Judge Theodore McMillian: Beacon of Hope and Champion for Justice - Karen L. Tokarz (Washington University Journal of Law and Policy, 2022)
“Judge Theodore McMillian: Beacon of Hope and Champion for Justice” illuminates the heroic groundbreaking accomplishments of Judge McMillian, who was a trailblazer in Missouri courts. Judge McMillian was Missouri’s first Black judge to sit on the state circuit court, state appellate court, and federal appellate court. Professor Tokarz traces Judge McMillian’s early life and career to demonstrate his life-long dedication to challenging disparities in the community and in the legal system. She discusses the Judge’s role on the St. Louis City Circuit Court, especially the Juvenile Court where he pushed for the expansion of constitutional rights for juveniles; his groundbreaking criminal justice and civil rights decisions on the Missouri Court of Appeals; and his contributions to anti- discrimination jurisprudence during his tenure on the Eighth Circuit Court of Appeals. She also notes his role as community leader, as a founder of the Herbert Hoover Boys Club, first board chair of the Human Development Corporation, president of the Urban League, and board member of the Office of Economic Opportunity Legal Services Program. Professor Tokarz draws from her own experience with Judge McMillian to illustrate his extraordinary integrity, unbounded compassion, and abundant inspiration to law students, lawyers, judges, and all who care about equal justice for all.
Keywords: Judge Theodore McMillian; Missouri Judiciary